Looking at Illocutionary Speech Acts between Lecturer and Students in Simultaneous Use of Different Online Learning Platforms - Riski Amrina Sari; Sistia dinita (Faculty of Humanities, Diponegoro University, 2022)
Lecturers, in the post-Covid-19 era, often used more than just one online platform to carry out the learning process. However, existing speech acts studies tend to focus on a dataset sourced from one online learning tool. There is a research gap on the illocutionary speech acts occurring in-class sessions where the lecturer and students used different learning tools at the same time for their lessons. Thus, this study aims to identify the most dominant illocutionary acts in a novel dataset comprised of lecturer-student interactions across (pre-activities) Zoom, (during and post-activities) Google Classroom, and WhatsApp throughout an entire semester (6 months) of first, third and fifth semesters EFL students of STBA Pontianak. This descriptive qualitative study tried to identify the five illocutionary speech acts according to Searle’s (1979) theory in the interactions between the lecturer and students across the three online learning platforms. Data on the participants’ utterances were collected via observation, recording, note-taking, and transcription. The data from 523 utterances were transcribed and carefully reduced to the required data based on the research question. Results showed four types of illocutionary speech acts occurred in different frequencies: assertive (114 utterances), directive (143 utterances), expressive (250 utterances), and commissive (16 utterances). The declarative type was not found, a pattern that was often present in previous studies, thus this study’s findings are in contrast to the majority of literature’s assertion that declarative is the type most dominant speech act used in the teaching-learning process. This research contributes a unique set of data and new considerations on the study of speech acts in online EFL classrooms.